LITERARY AND CULTURAL SIGNIFICANCE OF CONTEMPORARY SONG LYRICS - Mary Deliana Esther Dabukke (Adisam Publisher, 2025)
Song lyrics have become a powerful medium for expressing emotions, shaping identities, and addressing social and cultural themes in contemporary music. This study explores how lyrics function as literary texts with poetic structures and devices such as metaphor, narrative arc, and symbolism. It also examines their role in reflecting and influencing cultural values, linguistic trends, and collective consciousness. Drawing from selected examples across genres, the analysis reveals that lyrics often convey deeper meanings beyond their surface appeal, serving as tools for critique, resistance, and storytelling. As language becomes increasingly simplified in popular music, lyrics continue to adapt while maintaining their cultural relevance. The integration of literary analysis and cultural context demonstrates how lyrics articulate personal experiences and societal concerns, offering listeners a mirror to their realities and aspirations. Additionally, the global reach of English in songwriting highlights issues of identity, hybridity, and cross-cultural communication. By treating lyrics as both artistic and sociocultural expressions, this work emphasizes the enduring significance of words in music and their contribution to understanding contemporary life. The exploration affirms that lyrics are not merely accompanying text but essential components of meaning-making in modern musical compositions.